Determinan Keputusan Penggunaan Pembiayaan PNM Mekar Syariah pada Masyarakat Afdeling Pinang, Jember: Pendekatan Maqasid Syariah - Cica Adelia Veronika (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of financial literacy, service quality, and trust on the decision to use PNM Mekaar Syariah financing in the people of Afdeling Pinang, Silo District, Jember Regency with a sharia maqasid approach. The background of this research is based on the high use of PNM Mekaar Syariah financing by the people of Afdeling Pinang as one of the sources of meeting their needs and business capital, even though the majority of people have relatively low income levels and limited economic conditions in meeting their daily needs. The sharia maqasid approach is used to understand that the decision to use financing is not only based on economic considerations, but also on efforts to realize benefits through the use of financial products in accordance with sharia principles. This study uses a quantitative approach with multiple linear regression analysis techniques based on primary data obtained through the distribution of questionnaires to the people of Afdeling Pinang, Silo District, Jember Regency. The results of the study show that financial literacy has no effect on the decision to use PNM Mekaar Syariah financing. Meanwhile, the quality of service and trust have a positive and significant effect on the decision to use PNM Mekaar Syariah financing. These findings show that the community's decision to use PNM Mekaar Syariah financing is not only influenced by the quality of service and trust in the institution, but can also be understood as an effort to obtain benefits in accordance with the goals of maqasid sharia.
:: Finalisasi file repositori 31 Juli 2026_Kurnadi
Keywords: Financial Literacy; Service Quality; Trust; Financing Decisions; PNM Mekaar Syariah; Maqasid Syariah.